Studi Sebaran Lokasi Ritel Consumer Goods di Permukiman Tamalanrea Kota Makassar - Veronika Dora Pabuaran; Ananto Yudono; Ihsan Ihsan (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2013)
The existence of minimarket as the one of consumer goods retail activities around settlement residents needs to be considered, especially in its spread and radius service. It isoutlined in the SNI No. 03 Tahun 2004 about “Tata Cara Perencanaan Lingkungan Perumahan di Perkotaan” that is for the grocery store/stall (minimarket) can serve 250 people with 300 meters radius achievement. There are 15 minimarkets (2013) that lie at Bumi Tamalanrea Permai settlement and Telkomas Housing in Makassar City, it’s radius is not appropriate with standard and also don’t concern with traditional consumer goods. The main focus in this research are analyze the consumer goods retail typologyand correlation levelbetween the variablesinelection of retail locations. Descriptive and Map Overlay (GIS) analysis explain the consumer good retail typology that consists of 3, modern minimarket, semi minimarket, and stall. Correlation analysis explains the correlation levelbetween the variables inelection of retail locations, age, walking distance, income, hospitality services, and minimarket location are very significant. Based on that results, it will be required the appropriate idea of the consumer goods retail spreading so that prevalent radius service will take place.